The Impact of Fair Performance Appraisal to Employee Motivation and Satisfaction towards Performance Appraisal – A Case of PT. XYZ. - Christian Jonathan Cowandy (iBuss Management, 2014)
This research is conducted to find out employees’  perception about their performance appraisal system at PT. XYZ. The perception will be about how fair is the performance appraisal system of PT. XYZ, and how it can affect the employees’ motivation and their satisfaction towards the performance appraisal system itself.This research is conducted in PT. XYZ’s headquarter in Surabaya by distributing questionnaire to 80 employees of PT. XYZ from various different functions in the company. The data was analyzed using Multiple Linear Regression Analysis. The results shows that fair performance appraisal have significant impact on employees’ motivation to improve performance and satisfaction towards performance appraisal. Individually, all factors of fair performance appraisal have significant impact to employee’s  motivation, but for satisfaction towards performance appraisal, only procedure fairness has significant impact to satisfaction towards performance appraisal.  Keywords: Human Resources, Motivation, Employee’s Motivation, Satisfaction towards Performance Appraisal, Performance Appraisal